THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH IMPLEMENTATION ON WORK MOTIVATION AND PRODUCTIVITY IN XYZ FURNITURE PRODUCTION IN SLEMAN REGENCY - Hakim; Amelia Aminuddin A.P., Rezki (Journal of Vocational Health Studies, 2024)
Background: The XYZ furniture in Sleman Regency has three workstations: (1) Measuring and cutting, (2) Refining, and (3) Finishing. The production process in Micro, Small, and Medium Enterprises (MSMEs) still needs to implement OSH principles fully. Purpose: To determine how implementing occupational health and safety measures affects work motivation and productivity. Method: In this research, the Structural Equation Modeling (SEM) method was used, and all six employees were involved in the production process, aged 22 to 32 years. Result: The research demonstrates a significant positive impact of OSH implementation on work motivation (tcount = 3.477, p-value = 0.000), highlighting its substantial influence in enhancing employee motivation. Furthermore, a notable positive association is found between OSH implementation and work productivity (tcount = 3.653, p-value = 0.000), confirming the significant contribution of OSH practices to overall work productivity improvement. Additionally, the investigation reveals that work motivation significantly influences increased work productivity (tcount = 2.641, p-value = 0.008), underscoring the importance of cultivating motivation for enhancing workplace productivity. The highest influence value of the ten indicators (X24) is 9.18, which indicates work quality. Conclusion: The direct application of OSH substantially impacts on both work motivation and productivity. Moreover, a significant relationship is observed between work motivation and work productivity. Considering the utmost importance of work quality, improvements are recommended to enhance workstation design through a participatory ergonomics approach, and implementing the 5S concept in the furniture production area can effectively increase work quality.